2010
DOI: 10.1016/j.jasms.2010.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Desorption ionization by charge exchange (DICE) for sample analysis under ambient conditions by mass spectrometry

Abstract: An ambient pressure ionization technique for mass spectrometric analysis of substances present on solid surfaces was developed. A nebulized spray containing molecular ions of a solvent such as toluene can be generated by passing the solvent through a stainless steel capillary held at a high voltage. When the stream of charged droplets produced in this way is directed onto a solid surface, the analytes present on the surface are desorbed and ionized by a charge exchange process. This technique was shown to deso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 23 publications
0
33
0
Order By: Relevance
“…T he recently introduced desorption ionization by charge exchange (DICE) technique has been demonstrated to generate molecular ions from many classes of polar and nonpolar compounds under ambient conditions [1]. Upon further research work, we observed that the DICE technique does not produce gaseous metal cation adducts, even though they are commonly generated by other desorption methods.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…T he recently introduced desorption ionization by charge exchange (DICE) technique has been demonstrated to generate molecular ions from many classes of polar and nonpolar compounds under ambient conditions [1]. Upon further research work, we observed that the DICE technique does not produce gaseous metal cation adducts, even though they are commonly generated by other desorption methods.…”
Section: Introductionmentioning
confidence: 77%
“…The recently introduced DICE technique, on the other hand, has been demonstrated to generate gaseous molecular ions under ambient conditions from many polar and nonpolar compounds that possess ionization energies lower than that of the selected spray reagent [1]. We envisaged that a combination of the DICE and DESI techniques would enable the ionization of a broader range of analytes within a single desorption ionization experiment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the simulations also show that these organic projectiles made of large molecules require higher kinetic energies to overcome the regime of net deposition, an issue which could be avoided with inert projectiles such as noble gas clusters or organic clusters made of smaller, volatile molecules, such as toluene. 89 For this reason, the molecular clusters described in Reference 66 would not appear to be good candidates for molecular depth profiling and 3D analysis of organic materials. Another remarkable result of these simulations is that because of their large momentum, massive organic clusters under normal incidence also induce more molecular mixing in soft materials than fullerenes.…”
Section: Light-element Clustersmentioning
confidence: 99%
“…Although the formation of molecular ions by charge transfer has been noted under atmospheric conditions [6,[19][20][21][22], ambient MS methods generate primarily protonated molecules, or mixtures of molecular ions and protonated molecules. The outcome appears to be dependent on several factors (e.g., the strength of the discharge field, the possible presence of solvent and other chemical vapors, the nature of the gases used, and the temperature of the source).…”
Section: Introductionmentioning
confidence: 99%